2018
DOI: 10.1136/gutjnl-2017-314889
|View full text |Cite
|
Sign up to set email alerts
|

Improved adenoma detection with Endocuff Vision: the ADENOMA randomised controlled trial

Abstract: ObjectiveLow adenoma detection rates (ADR) are linked to increased postcolonoscopy colorectal cancer rates and reduced cancer survival. Devices to enhance mucosal visualisation such as Endocuff Vision (EV) may improve ADR. This multicentre randomised controlled trial compared ADR between EV-assisted colonoscopy (EAC) and standard colonoscopy (SC).DesignPatients referred because of symptoms, surveillance or following a positive faecal occult blood test (FOBt) as part of the Bowel Cancer Screening Programme were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
145
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 33 publications
12
145
1
2
Order By: Relevance
“…Six studies were eligible for the analysis of SSA/P detection rate. At least one SSA/P was detected in 15.5% of patients in the EAC group and 13.2% in the SC group.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were eligible for the analysis of SSA/P detection rate. At least one SSA/P was detected in 15.5% of patients in the EAC group and 13.2% in the SC group.…”
Section: Resultsmentioning
confidence: 99%
“…High‐definition colonoscopes aid in detection and are now widely considered fundamental to detection and effective treatments . Adjunctive devices and techniques have also been widely investigated, including chromoendoscopy and image‐enhanced endoscopy; mucosal exposure devices such as transparent hood, Endocuff, EndoRings,and the Third Eye Retroscope; and ultra‐wide‐angle endoscopes such as full‐spectrum endoscopy and the extra‐wide‐view colonoscope …”
Section: Introductionmentioning
confidence: 99%
“…The Endocuff, which is a flexible cap with two circle rows of plastic, hinged soft wings, has been developed to improve the ADR compared with SC . It flattens the mucosal folds during withdrawal and keeps the tip of the colonoscope steady during interventions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent example of this was the BSG supported Accuracy of Detection using Endocuff Optimisation of Mucosal Abnormalities study that delivered a 1700 patient multicentre RCT for an industry cost of approximately £150 000 plus free devices 7. The use of the Endocuff Vision device in this study was shown to significantly improve adenoma detection rates which has implications for a change in conventional practice.…”
Section: Initiatives and Solutionsmentioning
confidence: 81%